Effect of annealing in hydrogen atmosphere on ZnO films for field emission display. Issue 1 (November 2015) - Zulkifli, Zurita; Sharma, Subash; Shinde, Sachin; Kalita, Golap; Tanemura, M
Abstract: Surface morphology, crystallinity, conductivity and optical transmittance of ZnO films can be modified by annealing process. Hydrogen is one of the popular annealing gases as well as nitrogen, argon, oxygen and air which are commonly used for thin film cleaning or the removal of native oxide. In general, annealing is done at high temperatures (> 600degC) to improve the film properties. From a view point of environment, however, lower annealing temperature is preferable. In this work, low annealing process was challenged to understand the effect of annealing temperature on properties of ZnO thin films and nanostructured film grown on glass substrates for transparent field emission device applications. The annealing temperature employed was 100, 200 and 450°C at 100 sccm hydrogen flow rate. ZnO thin films were deposited by RF magnetron sputtering. The ZnO thin films were characterized by X-ray diffraction analysis (XRD), Atomic Force Microscopy (AFM), UV-VIS and Raman spectroscopy. The sheet resistances reduced about 15 kohm/sq at low annealing temperature. By contrast, the optical transmittance did not show any significant changes after annealing. The FE current density increased after the ZnO nanostructures film was annealed in 100°C. The results obtained could motivate a surface treatment for flexible ZnO thin film since the substrate is always suffered by heat.